Asset Valuation Model of Muntok White Pepper - Yudi Sapta Pranoto; Sumiyati Sumiyati (SOCA: Jurnal Sosial Ekonomi Pertanian, 2022)
Findings from the previous studies of asset valuation models on the plantation commodities were still provided double-edged evidence. Hence, this study aimed to examine the best model for economic valuation on the Muntok White Pepper through the Stochastic Modelling Approach. South Bangka, West Bangka, and Belitung Regency were selected as the study locations. Study participants were pepper farmers in the white pepper cultivation central area in Bangka Belitung. Primary data of the price, income, cash-flow, and production cost of the pepper commodity collected through observation and interview sessions with the participants. These data provided information for the volume production, cultivated land area, production cost, and land maintenance. Multiple regression models enrolled to analyze the collected data. The best asset valuation model was selected by employing Akaike’s Information Criterion (AIC) dan Schwarz Information Criterion (SIC).Results revealed that the market price approach had provided the best model for the asset valuation of the Muntok White Pepper. The price of the pepper was set speculatively by the farmer